EGFR Targeted Redox Sensitive Chitosan Nanoparticles of Cabazitaxel: Dual-Targeted Cancer Therapy, Lung Distribution, and Targeting Studies by Photoacoustic and Optical Imaging - Vikas N.; Mehata A.K.; Viswanadh M.K.; Malik A.K.; Setia A.; Kumari P.; Mahto S.K.; Muthu M.S. (My University, 2025)
In this research, we have modified tocopheryl polyethylene glycol succinate (TPGS) to a redox-sensitive material, denoted as TPGS-SH, and employed the same to develop dual-receptor-targeted nanoparticles of chitosan loaded with cabazitaxel (CZT). The physicochemical properties and morphological characteristics of all nanoparticle formulations were assessed. Dual-receptor targeting redox-sensitive nanoparticles of CZT (F-CTX-CZT-CS-SH-NPs) were developed by a combination of pre- and postconjugation techniques by incorporating synthesized chitosan-folate (F) and TPGS-SH during nanoparticle synthesis and further postconjugated with cetuximab (CTX) for epidermal growth factor receptor (EGFR) targeting. The in vitro release of the drug was seemingly higher in the redox-sensitive buffer media (GSH, 20 mM) compared to that in physiological buffer. However, the extent of cellular uptake of dual-targeted nanoparticles was significantly higher in A549 cells than other control nanoparticles. The IC50 values of F-CTX-CZT-CS-SH-NPs against A549 cells was 0.26 ± 0.12 μg/mL, indicating a 6.3-fold and 60-fold enhancement in cytotoxicity relative to that of dual-receptor targeted, nonredox sensitive nanoparticles and CZT clinical injection, respectively. Furthermore, F-CTX-CZT-CS-SH-NPs demonstrated improved anticancer activity in the benzo(a)pyrene lung cancer model with a higher survival rate. Due to the synergistic combination of enhanced permeability and retention (EPR) effect of small-sized nanoparticles, the innovative and redox sensitive TPGS-SH moiety and the dual folate and EGFR mediated augmented endocytosis have all together significantly enhanced their biodistribution and targeting exclusively to the lung which is evident from their ultrasound/photoacoustic and in vivo imaging system (IVIS) studies. © 2023 American Chemical Society.